(untitled) (Eduscotech, 2022)
This study aims to examine: (1) the research management standards implemented at Yogyakarta State University and Universiti Utara Malaysia, (2) the realization of research management standards achievement at both universities, and (3) the obstacles encountered in the implementation of research management standards at Yogyakarta State University and Universiti Utara Malaysia. This research employed a mixed-methods approach, combining quantitative and qualitative methods, using a comparative study design. Data were collected through document analysis, surveys, interviews, and observations related to research management practices at both institutions. The results indicate that the research management standards at Yogyakarta State University and Universiti Utara Malaysia are largely similar, encompassing key aspects such as planning, organizing, implementation, and monitoring and evaluation. In terms of realization, both universities manage research activities through dedicated university research institutes operating under the direct supervision of the Chancellor. Research management is carried out by the head of the research institute, who is responsible for planning, coordinating, implementing, and evaluating research activities in accordance with institutional policies and national regulations. However, several obstacles were identified in the implementation of research management standards, including administrative complexity, coordination challenges across academic units, and differences in regulatory frameworks between the two institutions. This study highlights that effective research management requires clear governance structures, strong leadership, and continuous evaluation to ensure the achievement of institutional research objectives.